The story of Muhammad Ali - Garrett, Leslie (New York DK Pub., 2002)
A brief biography of the legendary boxer who was the first to win the world heavyweight championship three times.
"A Dorling Kindersley book."
Includes index.
Keywords: Ali, Muhammad -- 1942-; Boxers (Sports) -- United States; Boxers (Sports); African Americans